The Impact Of Covid-19 Pandemic On Marital Relations - Case Study Kosovo: Array - Alishani Sopi, Detrina (Acta Universitatis Danubius. Juridica, 2020)
The Pandemic Covid-19, which hit the whole world, did not leave Kosovo untouched. In addition to causing health and economic damage, it also began to affect negatively people's psychosocial behaviors. As an unknown disease it caused a large number of deaths but left consequences and trauma even in family relationships. Due to the damage that Covid-19 caused and is causing in this paper I will made an analyses the impact of Covid-19 on family relations and the impact of Covid-19 on the increase of domestic violence. Kosovo is a young country but the phenomenon of domestic violence has been widespread even before, but since the pandemic Covid-19 appearance the number of reports of domestic violence has been increases for 19.37%., which in some cases have ended with fatality. The aim of this paper is to evaluate the influence of Covid-19 in increasing of this number and if had an impact on family issue in Kosova. During this paper, analytical and descriptive methods will be used to explain the impact of Covid-19 on marital relationships and recommendations to be given to overcome this situation. The data to be used will be qualitative obtained from already published documents and data obtained from cases occurring during the time of pandemic and isolation.